Expression of microRNAs related to apoptosis in the aqueous humor and lens capsule of patients with glaucoma - Yu, Hyo Seon; Hong, Eun Hee; Kang, Ji Hye; Lee, Yong Woo; Lee, Won June; Kang, Min Ho; Cho, Heeyoon; Shin, Yong Un; Seong, Mincheol (Frontiers in Medicine, 2024)
Background The aim of this study is to investigate the expression profiles of microRNAs (miRNAs) related to apoptosis in the aqueous humor (AH) and lens capsule (LC) of patients with glaucoma. Methods AH and LC samples were collected from patients with open-angle glaucoma and control participants who were scheduled for cataract surgery. A miRNA PCR array comprising 84 miRNAs was used to analyze the AH (glaucoma, n = 3; control, n = 3) and LC samples (glaucoma, n = 3; control, n = 4). Additionally, the AH and LC samples (glaucoma, n = 3; control, n = 4) were subjected to quantitative real-time PCR to validate the differentially expressed miRNAs determined using the PCR array. Bioinformatics analysis was performed to identify the interactions between miRNAs and diseases. Additionally, the differential expression of these miRNAs and the target gene was validated through in vitro experiments using a retinal ganglion cell (RGC) model. Results Expression levels of 19 and 3 miRNAs were significantly upregulated in the AH and LC samples of the glaucoma group, respectively (p < 0.05). Of these, the expression levels of hsa-miR-193a-5p and hsa-miR-222-3p showed significant differences in both AH and LC samples. Bioinformatics analysis showed experimentally validated 8 miRNA:gene pairs. Among them, PTEN was selected to analyze the expression level in AH and LC from separate cohort (glaucoma, n = 5; control, n = 4). The result showed downregulation of PTEN concurrent with upregulation of the two miRNAs in LC samples of glaucoma group. In vitro experiments validated that the expression levels of hsa-miR-193a-5p and hsa-miR-222-3p were significantly upregulated, and that of PTEN was significantly downregulated in the H2O2-treated RGC, while the level of PTEN was recovered through co-treatment with miR-193a inhibitor or miR-222 inhibitor. Conclusion This is the first study to investigate the differential expression of apoptosis-related miRNAs in the AH and LC of patients with glaucoma. Hsa-miR-193a-5p and hsa-miR-222-3p, which were upregulated in both AH and LC, may be considered potential biomarkers for glaucoma.